Writing by Drawing : When Language Seeks Its Other - Bellini, Andrea; Lombardi, Sarah; Centre d'art contemporain, Genève (Milan : Skira, 2020)
Douglas Abdell, Vincenzo Accame, Rosaire Appel, Tchello d’Barros, Gianfranco Baruchello, Tomaso Binga, Irma Blank, Nick Blinko, Alighiero Boetti, Marcia Brauer, Frédéric Bruly Bouabré, Elijah Burgher, Axel Calatayud, Gaston Chaissac, Laura Cingolani, Guy de Cointet, Aloïse Corbaz, Dadamaino, Betty Danon, Hanne Darboven, Michel Dave, Michael Dean, Mirtha Dermisache, Emmanuel Derriennic, Jean Dubuffet, Giordano Falzoni, León Ferrari, Chiara Fumai, Pepe Gaitán, Jill Galliéni, Ryan Gander, Anne-Marie Gbindoun, Marco Giovenale, Rafael González, Giorgio Griffa, Mariangela Guatteri, Gustav, Elisabetta Gut, Brion Gysin, Ana Hatherly, Emma Hauck, Takanori Herai, Joseph Heuer, Susan Hiller, Steffani Jemison, Carlo Keshishian, Annalies Klophaus, Maria Lai, Fabio Lapiana, Jürg Lehni, Dwight Mackintosh, Kunizo Matsumoto, Viviane Van Melkebeeke, Reinhold Metz, Henri Michaux, Miriam Midley, Bruno Munari, J.B. Murray, Gastone Novelli, Palanc, Giulio Paolini, Luca Maria Patella, Enzo Patti, Jean Perdrizet, Nathalie Perrin, Laure Pigeon, Renata Prunas, Justine Python, Svetlana Rabey, Carmen Racovitza, Judit Reigl, Jane Ruffié, Valeri Scherstjanoi, Salome Schmuki, Greta Schödl, Luigi Serafini, Jeremy Shaw, Hélène Smith, Ivana Spinelli, Martina Stella, Lina Stern, Laurence Sterne, Barbara Suckfüll, Jenna Sutela, Cecil Touchon, Louise Tournay, Jeanne Tripier, Pascal Vonlanthen, August Walla, Robert Walser, Galaxia Wang, Melvin Way, Adolf Wölfli
Scrivere Disegnando. When Language Seeks its Other, curated by Andrea Bellini and Sarah Lombardi, Centre d'Art Contemporain Genève, January 29 - August 23, 2020
boek